A bioethics reflection about the perspective of medical’ students about abortion and decriminalization (Saúde Ética & Justiça, 2022)
Abortion is defined by the World Health Organization as the termination of pregnancy before fetal viability. Despite the clear definition, abortion is a matter of bioethical relevance with several much-discussed controversies in the “bioethics of persistent situations." This article aims to assess the opinion of medical students from public and private universities regarding abortion, decriminalization, and the physician's duties in the face of an induced abortion. This survey included responses from medical students (n=110) to a self-administered structured questionnaire regarding the decriminalization of abortion. The results showed that most students (89%) are in favor of decriminalizing abortion in several situations, including cases where Brazilian law still does not allow it, such as in the case of malformations compatible with life and chromosomal alterations. In addition, students defend that the pregnant woman and the father should be the main ones responsible for deciding to carry out an abortion. Discussions about the bioethical implications of abortion and the physician's rights and duties in this context are fundamental, given the general ignorance on this subject.